2020
DOI: 10.3390/en13184843
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Energy Balance of Constructions Based on Wood during Their Use in Connection with CO2 Emissions

Abstract: In the construction industry, it is the material production phase and the use phase of buildings’ life cycles that represent the greatest environmental burden. The presented research focused on wood constructions during their use phase. The primary objective of the research was to determine the amount of CO2 produced during the operation of specific wood constructions in connection with the energy demand for their heating. A correlation analysis of selected parameters revealed a statistically significant corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…However, from the micro perspective, it is of more scientific importance and significance to promote the application of engineering technologies to reduce carbon emissions and increase carbon sink. These engineering technologies have the following aspects: reducing waste pollutants [65], reducing carbon emissions in agriculture [66], construction [67][68][69], the paper industry [70], and other industries, and increasing soil carbon absorption [66]. We cannot study these microscopic problems in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…However, from the micro perspective, it is of more scientific importance and significance to promote the application of engineering technologies to reduce carbon emissions and increase carbon sink. These engineering technologies have the following aspects: reducing waste pollutants [65], reducing carbon emissions in agriculture [66], construction [67][68][69], the paper industry [70], and other industries, and increasing soil carbon absorption [66]. We cannot study these microscopic problems in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Maldonado et al (2020) suggested that wood could boost job and wealth development for micro and smallsized businesses. The advantages of timber used in construction have also been widely shown in research, for example, lower energy consumption for production and lower carbon emissions of timber buildings compared to masonry ones, as verified by Gustavsson and Sathre (2006) and Oliver et al (2014), more efficient use of resources in the sustainability context for wood against masonry as studied by Svajlenka and Kozlovská (2018), the heating efficiency of timber houses as measured by Svajlenka and Kozlovská (2020a), wood solutions as lower carbon options in the life cycle as stated by Hart and Pomponi (2020), multiple uses of forestry species and wood products and efficient carbon fixation in different wood-based construction techniques as identified by De Araujo et al (2020b), and other contributions. However, Heräjärvi (2019) suggests that marketing on timber construction can be fallacious when, specifically, it is described as an effective tool to mitigate climate change since the effects of replacing traditional resources multiply the outcomes for physical carbon stocks.…”
Section: Introductionmentioning
confidence: 93%
“…Soluções baseadas em madeira é uma tendência da sustentabilidade global, resgatando os valores da utilização em moradias como ao longo da existência da humanidade (ZUBIZARRETA et al, 2019;ŠVAJLENKA;KOZLOVSKA, 2020a). E mesmo que ainda não seja a solução como resposta global para fins estruturais em edifícios, recentemente foi construído o maior edifício em madeira, o Mjøstårnet, em Brumunddal na Noruega, com 85,4 metros de altura (REMADE, 2021).…”
Section: A Madeira E O Seu Uso Na Construção Civilunclassified